Evaluating Guideline-Recommended Antibiotic Practices for Childhood Respiratory Infections: Is It Time to Consider Case-Based Formats?. (February 2016) - Wright, Heather; Skinner, Asheley Cockrell; Jhaveri, Ravi
Objective. We sought to better understand barriers to adherence to published guidelines for respiratory infections among community providers. Methods. A case-based survey was developed and emailed to all members of the state pediatric society. Providers chose their preferred management for acute otitis media, acute bacterial sinusitis, and community-acquired pneumonia. An "answer key" and a follow-up questionnaire were distributed to assess reevaluation of current practices. Results. We received 173 completed surveys (15% response rate). While most responders followed guideline recommendations (6 of the 10 questions with ≥65% choosing recommended antibiotic), discrepancies existed in several cases. After receiving the answer key, respondents said they reviewed the guidelines (69%), adjusted their practice (26%), used cases for teaching (9%), and discussed guidelines with colleagues (21%). Conclusions. The majority of respondents followed published guidelines, but there was a tendency to overuse azithromycin in certain cases. Future guidelines including case-based discussions may enhance adherence.